Aspects of the Javanese Language and Its Preservation - Supana, Supana; Sumarlam, Sumarlam; Suwanto, Yohanes (Proceeding of International Joint Conference on UNESA, 2025)
The current millennial era has witnessed a decline in the support for the preservation and advancement of Javanese as a mother tongue among the younger generation. The frequency of errors that transpire in the application of Javanese demonstrates the carelessness with which individuals employ the language. In actuality, each language has regulations about writing, linguistic combinations, pronunciation, and vocabulary choice, which serve as the foundation for language utilization. The frequent occurrence of errors in their application demonstrates that Javanese language users often fail to observe these principles adequately. Prevalent errors manifest in both written and spoken forms of the Javanese language. There are numerous misspellings, improper pronunciation, and inappropriate selections of speech levels. However, errors in the organization of Javanese sentences are a recurring problem, regardless of whether children, adolescents (the newer generation) or parents make them. Subjects that are not clearly defined are frequently found in sentences composed by speakers or writers. In addition, the arrangement of words into clauses or phrases, which is recurrently impacted by the utilization of Indonesian language structures, presents additional challenges. The persistent presence of Javanese vocabulary and various forms of ‘ngoko alus’ and ‘krama alus’ impede effective communication. Therefore, in the face of the onslaught of global culture, it is necessary to make serious and continuous efforts to protect, develop, and foster the Javanese language, literature, script, and culture in a structured and massive manner through the involvement of experts and practitioners as well as regional government intervention, so that they become true identities for their owners.